2006
DOI: 10.1161/circulationaha.106.627588
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Is Critical for Cardiac Sensory Innervation and Rescues Neuropathy in Diabetic Hearts

Abstract: Background-Molecular mechanisms regulating the cardiac sensory nervous system remain poorly understood. Cardiac sensory nerve impairment causes silent myocardial ischemia, a main cause of sudden death in diabetes mellitus (DM). The present study focused on the roles of nerve growth factor (NGF) in the regulation of the cardiac sensory nervous system and analyzed the mechanism of silent myocardial ischemia in DM. Methods and Results-We screened neurotrophic factors and found that cardiac sensory nerves develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 32 publications
(39 reference statements)
5
97
0
Order By: Relevance
“…In fact, Zahner et al report that vanilloid receptor-1-immunopositive sensory nerves are enriched in the epicardium but scarce in the myocardium (10). We show that cardiac sensory innervation is rich not only at epicardial sites but also in the ventricular myocardium and that sensory innervation increases with development (11). In a screen of several neurotrophic factors, we showed that development of cardiac sensory nerves coincides with synthesis of NGF in the heart.…”
Section: The Endothelin-1 (Et-1) / Ngf Pathway Is Critical For Cardiasupporting
confidence: 54%
“…In fact, Zahner et al report that vanilloid receptor-1-immunopositive sensory nerves are enriched in the epicardium but scarce in the myocardium (10). We show that cardiac sensory innervation is rich not only at epicardial sites but also in the ventricular myocardium and that sensory innervation increases with development (11). In a screen of several neurotrophic factors, we showed that development of cardiac sensory nerves coincides with synthesis of NGF in the heart.…”
Section: The Endothelin-1 (Et-1) / Ngf Pathway Is Critical For Cardiasupporting
confidence: 54%
“…Based on the present study, we formulate a possible theory for the susceptibility of the diabetic hearts to ischemic injury, which is that the damage of sensory nerve fibers induced by diabetes causes the decline in the expression and function of TRPV1, and the latter results in the deterioration of cardiac sensory function and consequently the failure of the perception of noxious signals, eventually rendering the diabetic hearts vulnerable to the ischemic injury. 30 As is mentioned above, TRPV1 is closely related with CGRP as CGRP coexists in the TRPV1-positive sensory nerves in the hearts of rats, pigs, and human. 31 The activation of TRPV1 results in the release of CGRP, which in turn exerts cardioprotective effects.…”
Section: Discussionmentioning
confidence: 91%
“…Upregulation of both NGF and GDNF was demonstrated in rats with Trypanozoma cruzi infection (Chagas disease) causing sympathetic as well as parasympathetic denervation (15). GDNF was also demonstrated to express in the hearts of murine embryos and neonates by quantitative RT-PCR (11). In addition, artemin, a neurotrophic factor of the GDNF family was shown to express along blood vessels in the early developmental stages and promote the development of sympathetic innervation of blood vessels (3,8).…”
mentioning
confidence: 99%